Wheel love / Syazwan Jehan Mohd Rizal - Mohd Rizal, Syazwan Jehan (2022)
Wheel love is a local skates shop that provides all types of skateboard and other skates sport item such as roller skate. It has been around for over 10 years in Malaysia and also one of the well known local skate shop. The idea of rebranding this brand is to make it more modern and approachable especially for the younger age to have the courage and interest to experience something new. the concept that I went with is to represent the local Malaysia element and implement it to the rebranding design to show the originality of the brand location.